The complete mitochondrial genome sequence of the Daweishan Mini chicken. (2nd January 2016) - Yan, Ming-Li; Ding, Su-Ping; Ye, Shao-Hui; Wang, Chun-Guang; He, Bao-Li; Yuan, Zhi-Dong; Liu, Li-Li
Abstract: Daweishan Mini chicken is a valuable chicken breed in China. In this study, the complete mitochondrial genome sequence of Daweishan Mini chicken using PCR amplification, sequencing and assembling has been obtained for the first time. The total length of the mitochondrial genome was 16, 785 bp, with the base composition of 30.26% A, 23.73% T, 32.51% C, 13.51% G. It contained 37 genes (2 ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes) and a major non-coding control region (D-loop region). The protein start codons are ATG, except for COX1 that begins with GTG. The complete mitochondrial genome sequence of Daweishan Mini chicken provides an important data set for further investigation on the phylogenetic relationships within Gallus gallus .